Indonesian emotion regulation scale for students based on reappraisal and suppression factor: The Rasch analysis - Waharjani Waharjani; Wahyu Nanda Eka Saputra; Dewi Afra Khairunnisa (Institute of Advanced Engineering and Science, 2023)
Every human being has emotional turmoil, which will be a serious problem if they cannot control it. The importance of emotion regulation has become one of the bases for developing a measure of emotion regulation for students, the Indonesian emotion regulation scale (IERS). No research yet describes an instrument that measures students’ level of emotion regulation in Indonesia. IERS consists of nine items in two aspects: reappraisal and suppression factor. The content validity test involves two experts in the field of psychometrics. In comparison, the construct validity test involved 354 high school students in Yogyakarta, Indonesia. Data analysis using inter-rater reliability (IRR) coefficient of Cohen’s kappa and Rasch analysis. Based on the study of the IRR coefficient of Cohen’s kappa, two experts agree on the acceptability of the IERS statement items. Besides that, the results of the application of Rasch analysis show that IERS is good, precise, and conforms with the model. IERS is a reliable and valid tool to measure students’ level of emotion regulation accurately. This paper discusses the implications and recommendations for further research for the implementation of guidance and counseling containing the value of emotion regulation as a follow-up to the performance of IERS.